Line-Frequency Phase-Controlled Rectifiers with Adaptive Digital Controllers - Vukic, Vladimir Đ. (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
This article deals with the influence of the PI controller linear gain scheduling on the dynamic characteristics of the line-frequency phase-controlled rectifier. The examined device has digital control electronics of the DRI 07B type, based on the Intel 80C196 microcontroller. The realized adaptive PI controllers utilize wide variations of the current gain (Kp), decreasing linearly in proportion to the increase of the rectifier output current in the area of the discontinuous currents. Reaching the threshold of the rectifier’s discontinuous current, the current gain of the PI voltage controller remains constant. Beside the improvement of the thyristor rectifier’s static stability during operation with small output currents, implementation of the adaptive PI control also led to improvement of the voltage controller response in the case of load disturbance in the range of 13–90% of the nominal rectifier output current. Transfer functions were analyzed for specific parts of the phase-controlled rectifier DRI 110-100 having nominal output parameters of 116 V and 100 A. The values of the relative damping and root locus were analyzed in detail.